2009
DOI: 10.1364/oe.17.023873
|View full text |Cite
|
Sign up to set email alerts
|

Measured optical constants of copper from 10 nm to 35 nm

Abstract: We use laser high-order harmonics and a polarization-ratio-reflectance technique to determine the optical constants of copper and oxidized copper in the wavelength range 10-35 nm. This measurement resolves previously conflicting data sets, where disagreement on optical constants of copper in the extreme ultraviolet most likely arises from inadvertent oxidation of samples before measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
1
9
0
1
Order By: Relevance
“…This result was unexpected because oxidation rates previously reported on bulk samples suggest a slower room-temperature oxidation rate, approximately 0:37 nm=h [18,19]. This rate suggests that we should have been able to see the oxide thickness growing, something we recently observed for copper [7]. Atomic force microscope (AFM) measurements showed that our uranium films had less than 1 nm rms roughness on a 1 μm × 1 μm scale.…”
Section: Deposition Of Uranium and Measurementssupporting
confidence: 62%
See 1 more Smart Citation
“…This result was unexpected because oxidation rates previously reported on bulk samples suggest a slower room-temperature oxidation rate, approximately 0:37 nm=h [18,19]. This rate suggests that we should have been able to see the oxide thickness growing, something we recently observed for copper [7]. Atomic force microscope (AFM) measurements showed that our uranium films had less than 1 nm rms roughness on a 1 μm × 1 μm scale.…”
Section: Deposition Of Uranium and Measurementssupporting
confidence: 62%
“…Unfortunately, the optical properties of relatively few materials are well-characterized in this wavelength range [4][5][6]. For example, we recently found that accepted optical constants for copper in the EUV were incorrect due to inadvertent sample oxidation [7]. A lack of experimental characterization is especially common for materials in the actinide series, where reactivity, toxicity, and (sometimes) radioactivity adds challenges to taking optical measurements.…”
Section: Introductionmentioning
confidence: 99%
“…So, in our deposition case, the thickness of copper was in the sub-micrometer range. The absorption depth of copper in the visible range of the light spectrum is tens of nanometers 32 33 34 35 and is the order of magnitude smaller than the thickness of deposited copper layer. Therefore, the colour was not influenced by the thickness of the metal layer.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the ϵ 1 and ϵ 2 as obtained here for Cu with values derived from reflection electron energy loss spectroscopy by Werner et al ., Hajati et al ., and by optical means by Johnson and Christy, Brimhal et al ., and Hagemann et al . The insert shows the low‐energy region on an expanded scale.…”
Section: Resultsmentioning
confidence: 99%